The Current Status of Corporate Social Responsibility Disclosure of Islamic Shari-based Banking Companies in Bangladesh - Hossain, Md. Sumon; Neogy, Taposh Kumar (American Journal of Trade and Policy, 2019)
The purpose of this study is to examine the current extent and any difference (if any) of CSR disclosure of Islamic Sharia-based banking companies in Bangladesh during the period of 2011-2015.  Content analysis is adopted to accumulate the data from company’s annual reports. The CSR checklist comprise of sixteen dimensions (including 85 items) of CSR activities i.e., ‘Environment’, Disaster management, ‘Sports, Shelter, Women, Disabled, Liberation war, Health, Education, Energy, Minorities, Employee, Product responsibility, IT, Community and Government. The study reveals that the grand mean disclosure of CSR information in annual report of Islamic banks is 25.89% with a standard deviation of 5.49%. Empirical evidence provides that there is statistically significant difference of CSR disclosure among Islamic Sharia-based banking companies in Bangladesh. But there is no significant difference of CSR disclosure of Islamic banking industry in Bangladesh year to year. Moreover, CSR disclosure of Islamic Shari-based banking companies is not diversified rather concentrated on some specific dimension and items of CSR. The study is mainly based on annual reports for the financial year 2011-2015 of Islamic Sharia-based banking companies in Bangladesh. Hence, the conclusion reached cannot be generalized.
Keywords: Corporate Social Responsibility; Disclosure; Islamic Sharia-based banking companies; Bangladesh